Between Djelfa Diary and Almond Field by Max Aub and Tales from Alicante and Albatera by Jorge Campos (Global Journal of Human-Social Science, 2023)
The article describes the relationship between Max Aub and Jorge Campos and how both fictionalized their respective stays in concentration camps
Keywords: max aub jorge campos concentrations camps correspondence alicante albatera